Avoiding Adverse Events after Postpartum Hospital Discharge. Issue 2 (March 2017) - Simpson, Kathleen Rice
Abstract : The hospital discharge process for new mothers and babies after childbirth is not always as comprehensive and individualized as it should be. Recommendations from the Agency for Healthcare Research and Quality for avoiding adverse events after hospital discharge are discussed and applied to postpartum and newborn care.